Training of trainers on climate-smart livestock feed resourcing options for Tigray, South Ethiopia, and Afar regions - Desta, Hiwot; Adie, Aberra; Lemma, Mamusha; Bezabih, Melkamu; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
The training of trainers on climate-smart livestock feed resourcing options for Tigray, South Ethiopia and Afar regions, held on 25–26 June 2025 took place at International Livestock Research Institute (ILRI) in Addis Ababa, with practical sessions conducted at the ILRI Bishoftu Genebank field site, the herbage seed unit, and a private feed processing and multi-nutrient block manufacturing plant in Adama. This training was part of the Restoration of Livestock Services in Conflict and Drought-Affected Areas of Ethiopia (RESTORE) project.